Pengembangan Supervisi Berbasis Masyarakat - Muhammad Idrus (Islamic University of Indonesia, 2008)
Quality is still being the main focus in education. And to improvingthe quality of education is not an easy task, which can be done ina short period and can not rely solely to school it self. In that processmany components that are expected to play an active role, include thecommunity as one of the stakeholders. The society has a significant rolein developing and improving the quality of education in schools. Byadopting the concept of School based management, the community cando the function of supervision of school performance or the function ofassessment in the success of the educational process; and together withthe school to arrange the school budget. In the educational system whichempowering the community, the society could determining the policies tobe taken by the school, the community will have more power to determineor to assess whether or not the performance of teachers and principals isgood enough or not. so in the future we must motivated the society to bea partner of school, and together with school to arrange the activity toimprove the quality in education